Composição química, digestibilidade e estabilidade aeróbia de silagens de milho colhidas em diferentes estádios de maturidade - Rabelo, Carlos Henrique Silveira [UNESP]; de Rezende, Adauton Vilela; Rabelo, Flávio Henrique Silveira; Basso, Fernanda Carvalho [UNESP]; Härter, Carla Joice [UNESP]; Reis, Ricardo Andrade [UNESP] (My University, 2015)
The objective of this study was to evaluate the effect of corn plant harvested in diferente ma-turity stages on the chemical composition, digestibility and aerobic stability of silages. The corn used in the study was the hybrid BM3061 harvested after 114, 121, 126, 133 and 140 days of sowing at five maturity stag-es based on the advancement of the grain milk line (early dent (ED), 1/3 of milk line (ML), 1/2 ML, 2/3 ML and black layer (BL)). A variation from 242.7 to 377.4 g of dry matter (DM) kg-1as fed was observed between the ED and BL stages; however, the measurements performed in this study did not exhibited major changes in the composition of these silages. The silages produced with plants that were harvested at the 1/2 ML, 2/3 ML and BL stages showed lower DM loss during the fermentative process. The silages produced with plants that were harvested at the ED and 1/3 ML stages showed higher in vitro organic matter digestibility (IVOMD) (0.584 and 0.631 g g-1 of OM, respectively). The corn silages produced at the maturity stage of 2/3 ML showed a higher aerobic stability (104 hours) during the aerobic exposure. The 1/3 and 2/3 ML maturity stages seem to be the best harvest stages for the production of corn silage in tropical climates.
Chemical composition, digestibility and aerobic stability of corn silages harvested at different maturity stages
Keywords: Digestibility; Fermentation; Fiber; Tropical climate